The OHADA Structure as a Possible Model for the Development of a Commercial Law Structure in the Southern African Development Community (SADC) - Leno, Ngaundje Doris (International Journal of Social Sciences and Management Review, 2020)
The Southern African Development Community's (SADC) colonial legacy which introduced foreign legal traditions and the consequences of the diversity heighten the urgency for unified commercial legislation to deal with cross-border disputes.Thus, the issue is whether the Organisation for the Harmonisation of Business Law in Africa (OHADA) structure can serve as a possible model for the development of a uniform commercial law structure in the SADC .Despite the success of the OHADA, the author submits that the OHADA can only serve as a source of inspiration, or roadmap, providing guidance to the SADC drafters.The paper aims at demonstrating that the OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC.The significance of this paper lies in the contributions it makes to the development of a commercial law structure in the SADC.
Keywords: Development; Integration; Model; OHADA; SADC